2019
DOI: 10.1146/annurev-med-081117-041238
|View full text |Cite
|
Sign up to set email alerts
|

Metformin for Treatment of Fragile X Syndrome and Other Neurological Disorders

Abstract: Fragile X syndrome (FXS) is the most frequent inherited form of intellectual disability and autism spectrum disorder. Loss of the fragile X mental retardation protein, FMRP, engenders molecular, behavioral, and cognitive deficits in FXS patients. Experiments using different animal models advanced our knowledge of the pathophysiology of FXS and led to the discovery of many targets for drug treatments. In this review, we discuss the potential of metformin, an antidiabetic drug approved by the US Food and Drug Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 102 publications
1
51
0
Order By: Relevance
“…Metformin lowers the level of blood glucose by enhancing peripheral glucose uptake and glycolysis while inhibiting hepatic gluconeogenesis and gastrointestinal glucose absorption. 3 The reduction of blood glucose causes a decrease of insulin signaling and consequently inhibits the mechanistic target of rapamycin complex 1 (mTORC1) and MAPK/ERK pathways. Moreover, metformin also inhibits the mTORC1 and ERK pathways via activation of AMPactivated protein kinase complex (AMPK) 3 .…”
Section: Metforminmentioning
confidence: 99%
See 2 more Smart Citations
“…Metformin lowers the level of blood glucose by enhancing peripheral glucose uptake and glycolysis while inhibiting hepatic gluconeogenesis and gastrointestinal glucose absorption. 3 The reduction of blood glucose causes a decrease of insulin signaling and consequently inhibits the mechanistic target of rapamycin complex 1 (mTORC1) and MAPK/ERK pathways. Moreover, metformin also inhibits the mTORC1 and ERK pathways via activation of AMPactivated protein kinase complex (AMPK) 3 .…”
Section: Metforminmentioning
confidence: 99%
“…3 The reduction of blood glucose causes a decrease of insulin signaling and consequently inhibits the mechanistic target of rapamycin complex 1 (mTORC1) and MAPK/ERK pathways. Moreover, metformin also inhibits the mTORC1 and ERK pathways via activation of AMPactivated protein kinase complex (AMPK) 3 . MMP-9 which is upregulated in conditions of FMRP deficiency causes a negative impact on synaptic formation in FXS.…”
Section: Metforminmentioning
confidence: 99%
See 1 more Smart Citation
“…The symptoms in patients with fragile X syndrome (FXS; phenotype MIM number: 300624) are related to the absence or deficiency of FMRP, a protein which plays a key role in protein translation which is important for neuronal synaptic connections. There is an upregulation of the metabotropic glutamate 5 (mGluR5) pathway, the insulin receptor and the mTOR pathway in the absence of FMRP (Gantois, Popic, Khoutorsky, & Sonenberg, 2019;Hagerman et al, 2017). This dysregulation leads to global developmental delays in males and continued IQ decline in childhood and adolescence (Wright-Talamante et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The use of metformin in the animal models, such as Drosophila FXS and FXS knock out (KO) mouse demonstrated that metformin could improve FXS phenotypes, the circadian rhythm deficits and memory deficits (Gantois et al, 2017;Monyak et al, 2017). Pathogenically overactive signaling pathways in FXS in the central nervous system could also be normalized by metformin (Gantois et al, 2017(Gantois et al, ,2019.…”
Section: Introductionmentioning
confidence: 99%